Analysis of Total Phenols, Total Flavonoids and Anthocyanin Levels in Blue Pea Flowers (Clitoria ternatea L) - Fira Kuswandari; Ernawati Sinaga; Nurbaiti Nurbaiti; Ali Husni (Universitas Nasional Jakarta, 2022)
This study aims to determine the content of total phenol, total flavonoid, and anthocyanin levels in flower telang flower (Clitoria ternatea L). Observations were made using different methods and solvents. Telang flower (Clitoria teratea L) extracted by maceration using ethanol solvent and dry extraction using water solvent freezedry method showed different content of total phenol, total flavonoid and anthocyanin content. The extract obtained was analyzed for its content using a UV-Vis spectrophotometer. The results showed that the average total phenolic content of flower telang flower was 2459.94 mgGAE/100g, total flavonoids 1171.10 mg/100g and anthocyanin content 122.79mg/100g. Meanwhile, the freeze-dry extract of the flower of telang flower showed an average total phenol content of 1924.96 mgGAE/100g, a total flavonoid content of 763.88 mg/100g and anthocyanin content of 890.49 mg/100g. The content of total phenol, total flavonoid and anthocyanin from ethanol extract was higher than that from water solvent. The ethanol extract and the water extract of the flower of telang flower have antioxidant potential in terms of the parameters of the total phenol content